An evaluation of osseous regeneration capability of novel autogenous tooth graft along with orthobiologics for long bone segmental defects - N. Hussain; M.A. Khan; A.K. Mahmood; M.Y. Tipu; S. Aslam (Heliyon)
Extracted tooth, is predominantly considered a medical waste but tooth and bone evince similitude in biochemical composition, so tooth may be considered as bone graft material. We selected twenty-four adult rabbits with age and body weight ranges of 1–3 years and 2–4 kg respectively, regardless of sex and breed. These rabbits were allocated into four groups i.e., J, K, L, and M. Autogenous tooth graft was acquired from the individual's incisor. In group J (control), tooth graft alone was used at the mid shaft radius fractured site. For group K, tooth and bone marrow aspirate (BMA) were applied. In group L, tooth-platelet rich plasma (PRP) was administered while for group M, tooth-decellularized fish scale (DFS) was engrafted at the location. The research was conducted for 4 months and parameter evaluation was done on 0, 1st, 7th, 15th, 30th, 45th, 60th, 75th, 90th, 105th and 120th days. The therapeutic regimens were extensively appraised in terms of physiological vitals, hematology, serology, bone biomarkers, mechanical assessment, radiography and histomorphometric parameters. We noticed appropriate osteointegration of autologous tooth with the fractured site, good healing and bone remodeling in all groups with superior to lower trends in Tooth-BMA, Tooth-PRP, Tooth-DFS, and Tooth-solo groups respectively. Though usage of aforementioned regimens in-vivo needs further trials but overall, we may suggest that autogenous tooth is not only a novel and viable graft in solo but its healing capacity, osteointegration and firm callus formation can be augmented with appropriate orthobiologic materials and in future may be useful for bone defect treatments, not only in animals but humans as well.